Whey protein hydrolysate enhances HSP90 but does not alter HSP60 and HSP25 in skeletal muscle of rats. - Carolina Soares Moura; Pablo Christiano Barboza Lollo; Priscila Neder Morato; Luciana Hisayama Nisishima; Everardo Magalhães Carneiro; Jaime Amaya-Farfan (PLoS ONE, 2014)
Whey protein hydrolysate (WPH) intake has shown to increase HSP70 expression. The aim of the present study was to investigate whether WPH intake would also influences HSP90, HSP60 and HSP25 expression, as well as associated parameters. Forty-eight male Wistar rats were divided into sedentary (unstressed) and exercised (stressed) groups, and were fed with three different sources of protein: whey protein (WP), whey protein hydrolysate (WPH) and casein (CAS) as a control, based on the AIN93G diet for 3 weeks. WPH intake increased HSP90 expression in both sedentary and exercised animals compared to WP or CAS, however no alteration was found from exercise or diet to HSP60 or HSP25. Co-chaperone Aha1 and p-HSF1 were also increased in the exercised animals fed with WPH in comparison with WP or CAS, consistent with enhanced HSP90 expression. VEGF and p-AKT were increased in the WPH exercised group. No alteration was found in BCKDH, PI3-Kinase (p85), GFAT, OGT or PGC for diet or exercise. The antioxidant system GPx, catalase and SOD showed different responses to diet and exercise. The data indicate that WPH intake enhanced factors related to cell survival, such as HSP90 and VEGF, but does not alter HSP60 or HSP25 in rat skeletal muscle.